The Homo-Hetero Pairing Effect Correlation Coefficient : A Modified Correlation Technique for Social Science Studies - Bundala, Ntogwa Ng’habi (International Journal of Business, Management and Economics, 2022)
The study aimed to examine the pairing relationship between economic growth and psychological human behavior (psychological well-being) of the individuals by application of the homo-hetero pairing effect correlation coefficient technique. The cross-sectional data were used. The data were collected from 211 individuals randomly sampled from two regions in Tanzania. The data were analysed by homo-hetero pairing effect correlation coefficient and the results were compared to that of the Pearson correlation coefficient and simple regression model. The study found that economic growth and psychological well-being are positively changing in pairs, and the psychological well-being of the individual is the true enabler (optimal independent) of the linear modelling. The study concluded that the improvement of the psychological well-being of individuals significantly improves economic growth and not vice versa. Therefore, the paper recommended that psychological well-being-based initiatives should be established and encouraged in society as found to have a positive impact on economic growth. Moreover, the study specifically, recommends the application of the homo-hetero pairing correlation coefficient in studies of cardiology, neurology, epidemiology, psychology, economics, anthropology, sociology and other fields of the social sciences.